Entrepreneurial Roles of Home-stay Tourism in Gabhar-valley Banke, Nepal - Pathak, Jagat Raj; Oli, Lok Bahadur; Pant, Ram Kumar (Journal of Rapti Babai Campus, 2026)
This study investigates as an example of model sustainable tourism and rural entrepreneurship in western Nepal, Gabhar Valley Homestay program at Ward No. 1 in Baijanath Rural Municipality (Banke District). A place of many ethnic groups, Khas, Tharu and Dalit, a mixture of Khas Mishimi culture that is Not exactly pure Khas but Khas blended with influences from other Tibetan-speaking peoples Tibet, Nepal, Bhutan or Sikkim, Kham refers to part of Tibet and Amdo. is colorful and pleasant enough for development. Currently 27 families are operating homestays. The study shows how tourism, by surging into such hospitality activities as b&b-style homestays, cultural events (both traditional song festivals that stay close to their roots and home-tourism in the region whether as part of your travels or a separate trip altogether), sustainable wooden crafts and agriculture for local consumption, sustains people’s lives in a way that census data trustworthily detects. The survey results revealed that 63.77% of people who filled in the questionnaire were stayers - 30% and up for providers. 30% of the people earn between NPR 50,000 and NPR 100,000 a year from tourism. Nearly half are dependent on farming for their livelihood. This does not mean, however, that there are no problems in need of finding solutions, like poor digital access and infrastructure.